2021
DOI: 10.1101/2021.08.10.455737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential autoimmunity resulting from molecular mimicry between SARS-CoV-2 Spike and human proteins

Abstract: Thrombocytopenia, characterized by reduced platelet count, increases mortality in COVID-19 patients. We performed a computational investigation of antibody-induced cross-reactivity due to molecular mimicry between SARS-CoV-2 Spike protein and human thrombopoietin, the regulator of platelet production, as a mechanism for thrombocytopenia in COVID-19 infections. The presence of a common sequence motif with similar structure and antibody-binding properties for these proteins strongly indicate shared molecular mim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…A molecular mimicry map of SARS-CoV-2 was also generated [ 38 ], and earlier [ 39 ], autoimmune-linked MHC alleles (class I and class II) were published [ 38 , 40 , 41 , 42 , 43 , 44 ]. Emerging variants of concern, specifically the widespread Omicron variant, drew attention [ 45 , 46 , 47 ] without an Omicron-sourced autoimmunity focus, despite some literature with a broader or a different focus [ 48 , 49 , 50 ]. Changes in infectivity, prevention by vaccination, and other concerns [ 51 , 52 , 53 , 54 ], were of more interest.…”
Section: Introductionmentioning
confidence: 99%
“…A molecular mimicry map of SARS-CoV-2 was also generated [ 38 ], and earlier [ 39 ], autoimmune-linked MHC alleles (class I and class II) were published [ 38 , 40 , 41 , 42 , 43 , 44 ]. Emerging variants of concern, specifically the widespread Omicron variant, drew attention [ 45 , 46 , 47 ] without an Omicron-sourced autoimmunity focus, despite some literature with a broader or a different focus [ 48 , 49 , 50 ]. Changes in infectivity, prevention by vaccination, and other concerns [ 51 , 52 , 53 , 54 ], were of more interest.…”
Section: Introductionmentioning
confidence: 99%
“…Human TPO is a glycoprotein hormone that regulates the production of platelets, essential elements for blood coagulation (Kuter and Begley, 2002). Previously, we have shown that molecular mimicry between Spike and TPO may induce thrombocytopenia, a disorder with low blood platelet count (Nunez-Castilla et al ., 2021). The EMoMiS pipeline result provides further evidence that antibodies that recognize TQLPP in Spike may cross-react with TPO, causing the reduction of platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mimicry can also explain several unexpected side effects of the SARS-CoV-2 infection. We recently reported that molecular mimicry between SARS-CoV-2 Spike and human thrombopoietin (TPO) might induce thrombocytopenia in infected subjects (Nunez-Castilla et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mRNA molecule is "humanized" by inserting 5' and 3' untranslated regions (UTRs) ) on its two ends, sequences borrowed from long-lasting human mRNAs, and adding a long poly-A tail to further promote resistance to breakdown [14]. The spike protein shares regions of high molecular similarity with many important human proteins, and molecular mimicry may lead to autoimmune disease, especially because the vaccine induces a very strong antibody response [17].…”
Section: Modifications In the Vaccine Mrna Sequencementioning
confidence: 99%